Buletin Peternakan : EKSPLORASI DAN IDENTIFIKASI GULMA, HIJAUAN PAKAN DAN LIMBAH PERTANIAN YANG DIMANFAATKAN SEBAGAI PAKAN TERNAK DI WILAYAH LAHAN KERING LOMBOK UTARA - Ni Made Laksmi Ernawati, I Ketut Ngawit (Peternakan UGM, 2015)
Difficulties on weeds control and fodder scarcity in dry season are the major problems at dry land. Aim of this research was to identify and to explore the potency of several kinds of weeds, forages, and agricultural wastes that can be used as fodder, and further might be processed to make hay and silage.